Identification and Clinical Analysis of the First Nonsense Mutation in the PSEN1 Gene in a Family With Acute Encephalopathy and Retinitis Pigmentosa - You, Chunlin; Zeng, Weike; Deng, Lingna; Lei, Zhihao; Gao, Xinyi; Zhang, Victor Wei; Wang, Yidong (Frontiers in Neurology, 2020)
In the present study, we investigated the genetic variation in a family with acute encephalopathy and retinitis pigmentosa. Nine of 25 people in this family underwent genetic testing. Three family members, namely, the proband and the proband’s two sisters, showed symptoms resembling those of meningoencephalitis and simultaneously suffered from retinitis pigmentosa. Whole-exome sequencing and Sanger sequencing identified a heterozygous mutation, chr14: 73673106 c.881G>A (p.W294*), in the presenilin 1 (PSEN1) gene in these three family members, and the SWISS-MODEL server predicted the formation of a truncated protein. This mutation was not found in the asymptomatic family members. This mutation is a newly discovered nonsense mutation that results in a truncated protein. Although the current genetic evidences may indicate the likelihood of association, further investigations are needed to establish the genotype and phenotype relationship